The implementation of environmental policy in Ireland : lessons from translating EU directives into action - Connaughton, Bernadette (Manchester University Press, 2019)
This book explores the response of Ireland's political-administrative system to the implementation of environmental directives in the cases of waste management, water reform and biodiversity. Ireland represents the implementation challenges of a small EU member state with a weak background in environmental governance, and has struggled to adapt to the complexities of enforcing environmental rules. Using a theoretical framework inspired by traditional implementation analysis and insights from the Europeanisation literature, the book traces the implementation process in three directives. The main conclusion of this study is that Ireland's implementation performance in waste management, water and nature conservation is influenced by the low issue salience of environmental policy and the need to overcome structural problems in the public administration system to give effect to EU legislation.